Mesin Pemisah Dan Pembersih Biji-Bijian / Butiran Sebagai Bahan Baku Pakan Burung Olahan - Rofarsyam Rofarsyam (Semesta Teknika, 2008)
Bird feed  ingredient process has been done traditionally which uses winnow that moved up and down by hands, just reach 6 kg/hour by a worker, that containt of 5.75 kg of solid grains, 0.25 kg empety grains and dust. For rising work efficiency needs separating process and cleaning process bird feed ingredient between solid grains and empety grains and dust by mechanical. Those are by build bird feed ingredient separating and cleaning machine. Construction and working principle designed, according to theory of subtance free fall, which forced by horizontal windy force by blower and motored by electrical motor  ½ Hp 1450 rpm completed by belt and pulley transmition. Capacity of bird feed ingredient separating and cleaning machine can reach 90 kg/hour consist 86.25 kg solid grains and 3.75 kg empety grains and dust.